Nation of Cowards : Black Activism in Barack Obama's Post-Racial America - Ikard, David, 1972- (Book collections on Project MUSE., 2012)
In a speech from which Nation of Cowards derives its title, Attorney General Eric Holder argued forcefully that Americans today need to talk more-not less-about racism. This appeal for candid talk about race exposes the paradox of Barack Obama's historic rise to the US presidency and the ever-increasing social and economic instability of African American communities. David H. Ikard and Martell Lee Teasley maintain that such a conversation can take place only with passionate and organized pressure from black Americans, and that neither Obama nor any political figure is likely to be in the fo.